REGRESSION OF SURVIVAL DAGUM 3 PARAMETER LINK FUNCTION IN HIV/AIDS PATIENTS IN EAST JAVA - Mahmudah, Nur; Ningrum, Ifa Khoiria (PATTIMURA UNIVERSITY, 2024)
AIDS (Acquired Immuno Deficiency Syndrome) is is a symptom of blood cell disease which results in decreased immunity in humans. HIV/AIDS causes a decline in economic productivity, health, and environmental fields, so it needs treatment to reduce the spread of the disease in East Java. The spread of the HIV/AIDS virus is growing rapidly both in terms of region and pattern of spread. Therefore, it is necessary to have policies from the government to prevent the spread of HIV/AIDS through mathematical modeling to determine the actual and comprehensive factors that influence HIV/AIDS care. policies needed to handle and reduce HIV/AIDS in East Java. This study aims to determine the factors that influence the care of people with HIV/AIDS with Survival Regression modeling Dagum 3 Parameter link function. This model uses parameter estimation with a Bayesian analysis approach with the results that the factors that significantly influence the length of HIV/AIDS care in East Java are marital status (X5), absolute CD4 levels (X7), Suffering Stage (X8), Functional State (X9), and Therapy adherence (X10). These results indicate that marital status and condition characteristics of HIV/AIDS sufferers are important information in the socialization program for reducing HIV/AIDS in East Java.